Análise comparativa dos sistemas de pré-ajustagem de ferramentas de corte toolsetters e presetters - Zago, André Maurício (2018)
The current economic scenario, in a context of globalization, causes competition between companies to become more and more, and thus, the search for competitive advantages becomes a survival factor. The use of CNC machines in manufacturing processes in machining companies can be a competitive advantage as they are used to exploit the functionality and features they offer to avoid underutilization due to the high scheduling and / or scheduling of benefits that are proposed in the time of acquisition. In this scenario, new technologies in tools and equipment arise with the objective of maximizing the use of available technology in CNC machines, in order to increase productivity and quality, generating cost reduction in manufacturing processes. Presetting systems are seen as a source of competitive advantage because they optimize machine configuration operations from time to time as well as the quality of machined parts. The present work aims to verify the similarities and differences in the benefits presented by two different types of presetting systems for existing machining tools: PRESETTER (external preset) and TOOLSETTER (internal preset). To do so, in addition to an analysis of the bibliographic review to identify the advantages of using each system, an experimental analysis performed the machining of samples, verifying the predefined time aspects of the tools and the dimensional quality aspects of the machined parts. The results show that each type of system has its own benefits and advantages and also some similar ones, and that both predetermination systems contribute to the reduction of the preparation times of the machine and that the two systems can complement each other to generate the time of gains and quality in machined parts.